Evaluation of silica content in winter wheat chaff. Issue 1 (13th August 2020) - Carter, A. H.; Rath, B. B.; Gorzkowski, E. P.; Qadri, S. B.
Abstract: There has been growing interest in finding alternative markets for excess field wheat ( Triticum aestivum L.) chaff residue. Recent studies indicate wheat chaff contains an abundant amount of silica (SiO2 ) in the amorphous state along with hydrocarbons. We examined the chemical composition of wheat chaff of four winter wheat cultivars with an emphasis on silicon content. After sample preparation, high resolution X‐ray diffraction and fluorescence were used to determine the amount of Si found in wheat chaff. Heat treatments were also applied to convert SiO2 to silicon carbide (SiC), which can be used in industrial nanoparticles and electronics. We found that the four wheat cultivars tested have differing amounts of Si in the chaff. Those with high amounts of Si can have the Si converted, through a simple heat‐treatment process, to SiC. Although research needs to be expanded to test additional cultivars and examine environmental influences, our results point to an interesting potential for the use of excess wheat chaff residue.